The Influence of Knowledge, Motivation and Supervision Techniques on Nurses' Compliance in Implementing Fall Risk Prevention in the Inpatient Room of Tiara Hospital Tangerang - Masriah, Masriah; Pamungkas, Rian Adi; Andry, Andry (International Journal of Nursing and Health Services (IJNHS), 2025)
Introduction: Implementing patient safety such as reducing patient risk of falling requires SOP. In 2023, the nurse compliance rate in conducting fall risk assessments at Tiara Hospital was 97%. Objective: This study was conducted to analyze various factors that influence nurse compliance in implementing fall risk prevention SOPs at Tiara Hospital Tangerang. Method: The type of research is analytical with an observational approach and using a Cross Sectional study. Questionnaires were distributed to 73 nurses. The dependent variable is Nurse Compliance in implementing the Fall Risk Prevention SOP, the independent variables of the study are Knowledge, Motivation and Supervision Techniques of the Head of the Room. Result: The results of the study showed that simultaneously knowledge, Motivation and Supervision techniques of the Head of the Room had a significant effect on Nurse compliance in implementing the Fall Risk Prevention SOP in inpatients at Tiara Hospital Tangerang. R square of 0.734 means that the variable can explain the influence of knowledge, motivation and supervision techniques of the Head of the Room by 73.4%. Recommendation: It is recommended that the management try to improve knowledge through training both internally and externally to the hospital and commitment in implementing SOP for preventing patient false